Biomimetic Platforms for Tissue Engineering. Issue 9 (2nd October 2013) - Vunjak‐Novakovic, Gordana
Abstract Bioengineering platforms that combine cell/tissuespecific transport and signaling with precise control of culture conditions and multiparametric insights into the cell function are critical to our efforts to study tissue development, regeneration, and disease under conditions that predict the human in vivo context. Because living cells respond to the entire context of their environment – in vivo and in vitro, under normal and pathological conditions – the biological foundation of our bioengineering designs that is often described as the "biomimetic paradigm" is critical for unlocking the biological potential of the cells. This brief review focuses on some of the key principles for designing and using biologically inspired engineering platforms. Four examples are used to illustrate the designs and applications of biomimetic platforms.